2022
DOI: 10.1002/mop.33322
|View full text |Cite
|
Sign up to set email alerts
|

Wideband dual‐polarized antenna with high isolation for full‐duplex application

Abstract: A wideband dual-polarized antenna with high isolation is proposed for full-duplex applications. It consists of a radiating patch, two E-shaped strips, a parasitic patch, a metal reflector, and a 180°power divider. Two hook-shaped strips and a pair of E-shaped strips are used to excite the radiating patch realize ±45°polarization. The impedance matching is significantly enhanced by the attendance of the parasitic patch and 180°power divider. Multiple decoupling techniques, including polarization diversity, radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In this scheme, a reflective terminal is used to cancel the direct coupling between the transmit and receive antenna. Whereas by employing differential feeding schemes and/or 180 °hybrid couplers for patch antenna, interport isolation ranging from 40 to 90 dB can be achieved [4][5][6][7][8]. However, it can be observed that high levels of isolation are achieved at the cost of bandwidth.…”
Section: Introductionmentioning
confidence: 99%
“…In this scheme, a reflective terminal is used to cancel the direct coupling between the transmit and receive antenna. Whereas by employing differential feeding schemes and/or 180 °hybrid couplers for patch antenna, interport isolation ranging from 40 to 90 dB can be achieved [4][5][6][7][8]. However, it can be observed that high levels of isolation are achieved at the cost of bandwidth.…”
Section: Introductionmentioning
confidence: 99%